New data on Himalayan Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) with description of a new species from Nepal - Shavrin, Alexey V. (Zootaxa, 2015)
Lesteva (s.str.) hartmanni sp. n. (Nepal: Gandaki Province, Manaslu Mts.), L. (s.str.) brevipennis Cameron, 1941 and L. (s.str.) torrentum Cameron, 1924 are (re-) described and illustrated. New records of L. (s.str.) championi Lohse, 1982, L. (s.str.) jaegeri Shavrin, 2012 and a modified identification key to the species of Lesteva Latreille, 1797 of Nepal are provided. L. brevipennis is recorded from Pakistan for the first time.